Preview, Question, Read, Reflect, Recite, Review Learning Strategy on Mathematical Ploblem-Solving Ability with the Assistance of Mural Software - Nur Fadhilah; Rohantizani Rohantizani; Amam Taufiq Hidayat; Erna Isfayani; Nur Elisyah; M Mursalin (SAINTIS Publishing, 2025)
The low level of students mathematical problem-solving ability remains a challenge in mathematics education, often resulting from limited engagement, lack of active reading, and ineffective instructional strategies. This study aimed to investigate the effect of the PQ4R (Preview, Question, Read, Reflect, Recite, Review) learning strategy on students mathematical problem-solving ability, supported by Mural software as a digital learning aid. The research employed a quantitative approach using a quasi-experimental design involving two tenth-grade classes at SMA Negeri 1 Kuta Makmur. The experimental group received instruction using the PQ4R strategy integrated with Mral software, while the control group wa taught using conventional methods. Data were obtained through pretest and posttest consisting of essay questions based problem-solving indicators. The Mann-Whitney U test wa used for hypothesis testing. The findings show that the PQ4R learning strategy, when assistes by Mural software, has a significant effect on students mathematical problem-solving ability.